Pengaruh Promosi dan Kepuasan Pelayanan terhadap Keputusan Berinvestasi Melalui Persepsi Potensi Investasi (Studi Di Provinsi Kalimantan Selatan) - Fitriyani Fitriyani; Taharuddin Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
ABSTRACT This study aims to determine whether investment exhibitions, investment forums, information of investment potential on websites, information of investment potential on billboards, and service satisfaction have a direct effect on investment decisions, and indirectly affect investment decisions through perceptions of investment potential. This research is a quantitative research using SmartPLS 3 with Structural Equation Modeling (SEM) method, the research sample is investors who invest their capital in South Kalimantan Province continuously for the last three years and recorded on several work projects totaling 86 respondents. Based on the analysis carried out, it was found that investment exhibitions, investment forums, information of investment potential on websites, and information of investment potential on billboards which are part of investment promotion activities were not able to influence investment decisions, the variable that really affects investment decisions is perception investment potential, and service satisfaction variables can affect investment decisions only if mediated by the perceptions of investment potential variable.  Keywords: Promotion, Service Satisfaction, Investment Decision, Perception of Investment Potential